Flux‐pinning properties of nanocrystalline HfO2 added YBa2Cu3O7−δ superconductor. Issue 4 (9th December 2013) - Rejith, Pullanhiyodan Puthiyaveedu; Vidya, Sukumariamma; Vipinlal,; Solomon, Sam; Thomas, Jijimon Kumpukattu
<x xml:space="preserve">Abstract</x> The effect of addition of different weight percentages of nanocrystalline HfO2, synthesized through a modified combustion method in bulk coarse‐grained orthorhombic YBa2Cu3O7−δ powder was studied. The structure and microstructure of the samples examined by X‐ray diffraction (XRD) and scanning electron microscopy (SEM) showed the formation of a secondary phase YBa2HfO5.5 in the superconductor without deteriorating the superconducting properties. The variation of sintering temperature, density, critical transition temperature (Tc), magnetic field dependence of critical current density (Jc), and flux‐pinning force (Fp) of YBa2Cu3O7−δ having different proportions of YBa2HfO5.5 formed in the matrix were studied in detail. The samples showed a transition temperature (Tc) of ∼92 K and the self‐field critical current density (Jc) increases significantly up to an optimum value of 5.42 × 104 A cm−2 for 2 wt% addition of nano HfO2. The enhancement of the critical current density in the YBa2Cu3O7−δ‐HfO2 samples is attributed to the presence of the nonreacting YBa2HfO5.5 phase, formed due to the addition of HfO2 as artificial pinning center. The formation of YBa2HfO5.5 in YBa2Cu3O7−δ bulk superconductor also enhances the pinning force density from 3 × 106 to 30.4 × 106 N m−3 at 77 K.